Karakteristik fisikokimia tepung rebung terfermentasi dan pati rebung terfermentasi dari bambu ampel kuning (bambusa vulgaris schrad var. striata) serta potensinya sebagai pengental [Physicochemical characteristics of fermented bamboo shoot flour and fermented bamboo shoot starch from yellow ampel bamboo (Bambusa vulgaris schrad var. striata) and their potential as thickeners] - Rohadi Rohadi; Adi Sampurno; Bambang Kunarto (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
This study aimed to characterize the physical and chemical properties of fermented bamboo shoot flour (TRF) and fermented bamboo shoot starch (PRF) and to test their potential as thickeners. The research was carried out in 4 stages: sample authentication, TRF preparation and characterization, PRF preparation and characterization, and PRF gelling testing at various pH. The results showed that TRF contained 23.92±0.33% insoluble fiber, 6.03±0.10% cellulose, 1.85±0.01% hemicellulose, 15.87±0.10% lignin, and soluble fiber. 2.91±0.03%. PRF had a density of 707 kg/m3, slightly dull color, and reddish brown. TRF cannot be used as a thickener due to it does not form a stable suspension and does not form a gel when heated, but it has potential as an animal feed with a value of acid detergent fiber (ADF) 22.18 and neutral detergent fiber (NDF) 2. 40. Meanwhile, PRF-tapioca has potential as a thickening agent because it formed a stable suspension and formed a gel when heated. Adding 0.5-2.5% PRF to 1%, tapioca suspension produced a gel viscosity of 6.4 – 8.5 cP., similar to 3 g/25 mL modified cassava flour gel formation.